Near‐Complete Local Reduction of Arctic Stratospheric Ozone by Severe Chemical Loss in Spring 2020. Issue 20 (9th October 2020) - Wohltmann, I.; von der Gathen, P.; Lehmann, R.; Maturilli, M.; Deckelmann, H.; Manney, G. L.; Davies, J.; Tarasick, D.; Jepsen, N.; Kivi, R.; Lyall, N.; Rex, M.
Abstract: In the Antarctic ozone hole, ozone mixing ratios have been decreasing to extremely low values of 0.01–0.1 ppm in nearly all spring seasons since the late 1980s, corresponding to 95–99% local chemical loss. In contrast, Arctic ozone loss has been much more limited and mixing ratios have never before fallen below 0.5 ppm. In Arctic spring 2020, however, ozonesonde measurements in the most depleted parts of the polar vortex show a highly depleted layer, with ozone loss averaged over sondes peaking at 93% at 18 km. Typical minimum mixing ratios of 0.2 ppm were observed, with individual profiles showing values as low as 0.13 ppm (96% loss). The reason for the unprecedented chemical loss was an unusually strong, long‐lasting, and cold polar vortex, showing that for individual winters the effect of the slow decline of ozone‐depleting substances on ozone depletion may be counteracted by low temperatures. Plain Language Summary: The severe stratospheric chemical ozone loss in the Antarctic ozone hole and its impact on human health and climate have generated widespread public, political, and scientific interest. In contrast, Arctic stratospheric ozone reduction has been much more limited because of higher temperatures and higher transport variability in the Northern Hemisphere (lower temperatures lead to more chemical loss, and more transport can increase ozone values). In the Arctic spring 2020, however, observations of balloon sondes and satellites show that locally, absolute values of ozone (measured in mixing ratios, i.e., molecules of ozone per molecules of air) are significantly lower than in any previous year and are comparable to typical local values in the Antarctic ozone hole, albeit over a much narrower vertical layer. Locally, the chemical loss of ozone peaked at 93% in the Arctic spring of 2020, compared to values of 95–99% in the Antarctic in most winters since the late 1980s. The reason for the unprecedented loss was unusually cold and stable conditions in the Arctic stratosphere. Key Points: Local minimum ozone mixing ratios of 0.1–0.2 ppm observed by sondes in Arctic spring 2020 are significantly lower than in any previous year Local ozone loss (93%) and low mixing ratios are comparable to typical values in the Antarctic ozone hole (95–99%, 0.01–0.1 ppm) The reason for the unprecedented chemical loss was an unusually strong, long‐lasting, and record cold polar vortex